Big cats like water: occupancy patterns of jaguar in a unique and insular Brazilian Amazon ecosystem - Duarte, Herbert O. B. (2023)
Patterns of detectability and occupation of the jaguar (Panthera onca) vary throughout its distribution, being determined primarily by vegetation cover, prey availability, and anthropogenic factors. However, there is still a large knowledge gap regarding what determines jaguar occupancy, especially in the Amazon. This knowledge gap is even more pronounced for oceanic islands, which represent unique and very sensitive ecosystems, such as the Maracá-Jipioca Islands of the Northeastern Brazilian Amazon. Our study aimed to establish the spatial ecology of jaguars in this insular ecosystem and to provide information to facilitate sustainable management of the population there. We assessed how different factors (vegetation type and prey availability) potentially influence detectability and occupancy patterns of the jaguars of the Maracá-Jipioca Islands. We found that greater wetland (beach-sea and lagoon-channel) cover was the main driver of jaguar detectability and occupancy. We revealed factors driving the population and spatial ecology of jaguars in an insular system. Despite imminent threats to the region, the knowledge we present can inform the sustainable management of jaguars to ensure that the fundamental and unique ecosystem services provided by this top predator are maintained.